Obesity, dietary diversity, and hypertension among posyandu attended child-bearing age women in Bandung - Astuti, Widya; Adha, As Syaffa Amalia; Anggraeni, Nuri (Universitas Gadjah Mada, 2025)
Purpose: This study explores the relationship between nutritional status and dietary diversity and the incidence of prehypertension and hypertension in women of reproductive age in Baleendah, Bandung Regency. Methods: The cross-sectional design, with primary data, was conducted from August to September 2023 in Baleendah Village, Bandung Regency, Indonesia. The study subjects were 50 women aged 15-49 years who registered at the Posyandu, had children aged 0-23 months, and had a history of hypertension, with the exclusion criteria being pregnant women. Nutritional status was measured using body weight with a digital scale and height with a SAGA multifunction tool. Food consumption data was collected through 24-hour dietary recall, and eating was assessed using a food frequency questionnaire (FFQ). Blood pressure was measured using a blood pressure monitor. The Minimum Dietary Diversity for Women (MDD-W) instrument measures dietary diversity diversity. The relationship between hypertension status and nutrient intake was analyzed using Spearman correlation tests applied due to non-normally distributed data. Results: There is a significant correlation between nutritional status and the incidence of prehypertension and hypertension in women of reproductive age (p-value=0.045). However, there is no significant correlation between dietary diversity and the incidence of prehypertension and hypertension in women of reproductive age (p-value=0.853). Conclusion: This study found a significant correlation between nutritional status, particularly obesity, and the incidence of prehypertension and hypertension in women of reproductive age, while dietary diversity showed no significant correlation. Economic and educational factors also played a role, with lower-income and less-educated respondents being more prone to hypertension. High consumption of fried snacks and high-sodium foods like salted fish and caffeine were associated with an increased risk of hypertension.